Pepys's navy the ships, men and organisation, 1649-89 - Davies, J. D. (Seaforth Publishing, 2008)
This new reference book describes every aspect the English navy in the second half of the seventeenth century, from the time when the Fleet Royal was taken into Parliamentary control after the defeat of Charles I, until the accession of William and Mary in 1689 when the long period of war with the Dutch came to an end. This is a crucial era which witnessed the creation of a permanent naval service, in essence the birth of the Royal Navy. Every aspect of the navy is covered - naval administration, ship types and shipbuilding, naval recruitment and crews, seamanship and gunnery, shipboard life